Analysis of Key Success Factors for Digital Transformation in Implementing Robotic Process Automation (RPA) at General Insurance Company PT.X - Butarbutar, Roni Daniel; Sutjipto, Mohammad Riza (International Journal of Scientific Research and Management (IJSRM), 2025)
• X is a general insurance company, has been implementing digital transformation in recent years by emphasizing three aspects: business processes, human resources, and governance and risk management. One of the strategic steps taken is the implementation of Robotic Process Automation (RPA) in business processes, especially in underwriting automation, in order to improve operational efficiency, expand market reach, and provide optimal service to customers. This study aims to identify key factors for the success of RPA implementation at PT. X. The research method used is qualitative, including interviews, observations, and data collection from stakeholders involved in the RPA project, such as strategic planners, managers, and end users. The theoretical framework used refers to the key factors for the success of RPA according to Schelgel et al. (2024), which are divided into three categories: human factors, organizational factors, and technical factors. The results of the study indicate that the success of RPA implementation at PT. X is influenced by several aspects, including: Human Factors (leadership and management support, engagement and communication, employee understanding and training, and change management), Organizational Factors (RPA strategy and vision, implementation scale and strategy, governance and organizational structure, risk management, process selection and prioritization, and process documentation), and Technical Factors (data and information security, infrastructure and technology readiness, system maintenance and development, and proof of concept). This study contributes to the understanding of RPA implementation by offering insights into the challenges and risks faced by companies or general insurance in carrying out digital transformation. The findings obtained can be used as a reference for other organizations that want to adopt RPA to improve operational efficiency and drive innovation.